rgins, widows and married womens: representations of the feminine in the Ambrosian discourse (4th century A.D.) - Dias, Larissa Rodrigues Sathler (Romanitas - Revista de Estudos Grecolatinos, 2018)
In analyzing the De Virginibus and De Viduis, ascetic treatises written by Ambrose, bishop of the Church of Milan (374-397), we sought to understand not only how the bodies of virgins, widows and married women were represented, but also to ascertain the formation of a female hierarchy within the Milanese community. Whereas the women’s status in the moral discourses produced by the fourth-century episcopal elite was paradoxical, because, on the one hand, at least on the spiritual level, women were presented in a degree of parity with men, and, on the other, on the ground, infirmitas of the feminine sexual nature stands up, this hierarchy seems to be responsible for foreseeing that virgins and widows, women who overcame the weakness of their bodies and became the model of all Christian chastity, occupy a position above married women.